English English - Novi Anty; Ardie Halim Wijaya (ALGOR, 2023)
During the current COVID-19 pandemic, many have lost their main jobs. Besides that, there are also many people who need a side job outside their main job for various reasons. There are also people who have the skill but find it difficult to find normal jobs. Then from the employer's side, many also find it difficult to find the best candidate that fits them. For this reason, an information system was built where this system will become a forum for job seekers and also employers, where job seekers can promote themselves according to their skills. Employers will also be able to easily find and select the best candidates according to what they want. This system will be built using the Extreme Programming (XP) methodology. This system will use the Heuristic Evaluation calculation method. After testing with usability aspects, it is known that this system needs to be repaired immediately because the calculation results show that the system is on a scale of 3 and is included in the category of major usability problems. It is hoped that this system will facilitate communication between employers and job seekers.